Biodegradable trimethyl chitosan nanofiber mats by electrospinning as bioabsorbable dressings for wound closure and healing - Anisiei, Alexandru; Andreica, Bianca-Iustina; Mititelu-Tartau, Liliana; Coman, Corneliu G; Bilyy, Rostyslav; Bila, Galyna; Rosca, Irina; Sandu, Andreea-Isabela; Amler, Evžen; Marin, Luminita (International journal of biological macromolecules, 2023)
The paper aimed to prepare quaternary chitosan-based nanofibers as bioabsorbable wound dressings. To this aim, fully biodegradable chitosan/N,N,N-trimethyl chitosan (TMC) nanofibers were designed and prepared via electrospinning, using poly(ethylene glycol) as sacrificial additive. The new biomaterials were structurally and morphologically characterized by FTIR and NMR spectroscopy, thermogravimetric analysis, X-ray diffraction and scanning electron microscopy, and their properties required for wound dressings application were investigated and discussed in detail. Thus, the nanofiber behavior was investigated by swelling, dynamic vapor sorption, and in vitro biodegradation in media mimicking the wound exudate. The mechanical properties were analysed from the stress-strain curves, the bioadhesivity from the texture analysis and the mucoadhesivity from the Zeta potential and transmittance measurements. The antimicrobial activity was assessed against S. aureus and E. coli strains, and the biocompatibility was tested in vitro on normal human dermal fibroblasts, and in vivo on rats. The application of the fiber mats with the best balance of properties as dressings on deep burn wound models in rats showed wound closure and active healing, with fully restoration of epithelia. It was concluded that the combination of chitosan with TMC into nanofibers provides new potential bioabsorbable wound dressing, opening new perspectives in regenerative medicine.
Keywords: nanovlákna; obvazy; Burn wound healing; Escherichia coli; Chitosan; Anti-Bacterial Agents; chitosan; lidé; krysa rodu Rattus; Staphylococcus aureus; antibakteriální látky; Rats; vstřebatelné implantáty; Nanofibers; Bioabsorbable; Bandages; zvířata; N,N,N-trimethyl chitosan nanofibers; Animals; Humans; Absorbable Implants